INNOVATIVE MSME DEVELOPMENT AND CREATIVE ENTREPRENEURSHIP POLICIES: A NEW PATH FOR THE LAMONGAN PEOPLE'S ECONOMY TO RISE TO A HIGHER LEVEL - Yuhronur Efendi; Muhammad Chusnul Khitam; Beni Aprilian Nirwansyah (RADJA PUBLIKA, 2026)
UMKM and creative entrepreneurs are the lifeblood of the Indonesian economy. However, the reality on the ground shows that the majority of UMKM remain micro-scale. Most tend to be subsistence, operate in the informal sector, are not connected to broader supply chains, have minimal access to formal financing, and are highly vulnerable to external shocks. Therefore, a method is needed to emphasize that regional economic independence is determined more by innovative local policies, strong social relationships, and cross-actor collaboration, rather than simply waiting for large investments. This research uses a qualitative descriptive approach. Research techniques included interviews, focus group discussions, documentation studies, and observations. The findings suggest that to create sustainable growth, innovation and productivity must be the primary focus. Without encouragement to innovate and building a strong supporting ecosystem, MSMEs risk stagnation. To achieve this, three essential foundations must be met: local institutions that support a conducive business climate, capacity and innovation to increase competitiveness and professionalism, and relationships between local actors that strengthen social networks and locally-based innovation capacity.